The Evolution of Emerging Nanovesicle Technologies for Enhanced Delivery of Molecules into and across the Skin - Elka Touitou; Hiba Natsheh (Pharmaceutics, 2024)
This review focuses on nanovesicular carriers for enhanced delivery of molecules into and across the skin, from their design to recent emerging technologies. During the last four decades, several approaches have been used aiming to design new nanovesicles, some of them by altering the properties of the classic phospholipid vesicle, the liposome. Phospholipid nanovesicular systems, including the phospholipid soft vesicles as well as the non-phospholipid vesicular carries, are reviewed. The altered nanovesicles have served in the manufacture of various cosmetic products and have been investigated and used for the treatment of a wide variety of skin conditions. The evolution and recent advances of these nanovesicular technologies are highlighted in this review.